2008
DOI: 10.1097/mop.0b013e3282f45bcf
|View full text |Cite
|
Sign up to set email alerts
|

Acute poststreptococcal glomerulonephritis: an update

Abstract: Severe group A streptococcal disease including acute poststreptococcal glomerulonephritis remains a cause of morbidity and mortality in developing countries and among impoverished populations. Various reports on the diverse clinical manifestations that can be associated with the condition will aid physicians in prompt diagnosis and intervention, while studies focusing on better understanding of immunopathogenesis may facilitate vaccine development and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 47 publications
(37 reference statements)
1
35
1
3
Order By: Relevance
“…Bingler et al reported APSGN generally in children above 6 years whereas Ahn et al obtanined lower in children under 2 years because of the immune complex system is still immature and pharyngitis incidence. 5,7 Statistical analyses did not show a significant difference between age and APSGN patient outcomes (p= 0.108) and same as the report by Mossie and Shimels. 3 However, Ahn and Suarta IK et al concluded that older children as poor prognostic factor.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Bingler et al reported APSGN generally in children above 6 years whereas Ahn et al obtanined lower in children under 2 years because of the immune complex system is still immature and pharyngitis incidence. 5,7 Statistical analyses did not show a significant difference between age and APSGN patient outcomes (p= 0.108) and same as the report by Mossie and Shimels. 3 However, Ahn and Suarta IK et al concluded that older children as poor prognostic factor.…”
Section: Discussionsupporting
confidence: 78%
“…3 However, Ahn and Suarta IK et al concluded that older children as poor prognostic factor. 6,7 Our study did not show a significant difference between nutritional status and outcomes (p= 1.000). Same result was reported by Mossie and Shimels in Ethiopia.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…2 Also, Etuk et al 7 reported 56% males and 44% females; 7 Albar et al 8 reported APSGN in 58.3% males and 41.7% females; 8 and Sepahi et al reported a male: female ratio of 1.23: 1. 9 According to Ahn et al 10 ,this discrepancy could be due to males more often engaging in activities outside the house, making them more likely to be exposed to BHAS. 10 The mean age of our subjects was 9.36 years, with a range of 3.42 to 14.67 years.…”
Section: Discussionmentioning
confidence: 99%